2019
DOI: 10.1128/aac.02281-18
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Mechanism, and Inhibition of Aspergillus fumigatus Thioredoxin Reductase

Abstract: Aspergillus fumigatus infections are associated with high mortality rates and high treatment costs. Limited available antifungals and increasing antifungal resistance highlight an urgent need for new antifungals. Thioredoxin reductase (TrxR) is essential for maintaining redox homeostasis and presents as a promising target for novel antifungals. We show that ebselen [2-phenyl-1,2-benzoselenazol-3(2H)-one] is an inhibitor of A. fumigatus TrxR (Ki = 0.22 μM) and inhibits growth of Aspergillus spp., with in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 88 publications
1
36
0
Order By: Relevance
“…This is corroborated by the observation that TrxR activities are essential in other fungi as well (Missall and Lodge, 2005), suggesting that it is a pan-fungal candidate. While the number of distinct and specific inhibitors of TrxRs of fungal origin is limited, aspects of ligandability and druggability might be addressed for the A. fumigatus enzyme based on its recently solved X-ray structure (Marshall et al, 2019). In line with this, our study adds to the growing body of knowledge on fungal TrxRs and specifically supports the hypothesis that it represents a promising target for antifungal therapy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This is corroborated by the observation that TrxR activities are essential in other fungi as well (Missall and Lodge, 2005), suggesting that it is a pan-fungal candidate. While the number of distinct and specific inhibitors of TrxRs of fungal origin is limited, aspects of ligandability and druggability might be addressed for the A. fumigatus enzyme based on its recently solved X-ray structure (Marshall et al, 2019). In line with this, our study adds to the growing body of knowledge on fungal TrxRs and specifically supports the hypothesis that it represents a promising target for antifungal therapy.…”
Section: Discussionsupporting
confidence: 70%
“…Recently it has been demonstrated that the established drug ebselen that targets TrxR enzymes of bacteria, fungi, or mammals (Azad and Tomar, 2014), strongly inhibits the A. fumigatus TrxR (Marshall et al, 2019). This is of special relevance as validated cellular targets and corresponding antifungal compounds are limited, raising severe concerns about future development of antimycotic therapy (Denning and Bromley, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The iodothyronine family of deiodinases comprises 3 isoenzymes, two of them being activators: DIO 1 and DIO 2 (converts T 4 to T 3 ) and one inactivator: DIO 3 which inactivates T 3. . (27) Thioredoxin reductase (TR) (28,29), (TR) is an enzyme that contains a selenocysteine residue in the terminal sequence and has three isoforms (TR 1, TR 2, TR 3). This catalyzes the reduction of NADPH-dependent thioredoxin as well as other oxidized cell constituents.…”
Section: The Pathway Of Selenocysteine Biosynthesis In Mammalsmentioning
confidence: 99%
“…There have been continual efforts to characterize enzymes involved in the biosynthesis of ergosterol or cell wall components, both of which are classic antifungal targets, to develop novel inhibitors (Urbina et al, 2000 ; Hata et al, 2010 ; Marshall et al, 2018 ). However, there has also been a notable shift in focus from these pathways exclusive to fungi to exploiting species-specific differences in shared pathways between fungi and humans (Rodriguez-Suarez et al, 2007 ; Marshall et al, 2017 , 2019 ; Kummari et al, 2018 ). To effectively establish infection, the fungus must adapt to a different niche within the human host, combat, or circumvent the host immune response and obtain sufficient nutrients to reproduce and disseminate.…”
Section: Introductionmentioning
confidence: 99%